Réponses

2013-04-13T08:45:12+02:00

x² + 6x + 9 = (x)² + 2 * 3 * x + (3²)

Donc x² + 6x + 9 = ( x+ 3)²

 

36 – 12x + x² = (6)² – 2 * 6 * x + (x²)

Donc 36 – 12x + x² = (6 – x)²

 

100 – 4x² = (10)² – (4x)²

Donc 100 – 4x = (2x + 5)(2x – 5)

2013-04-13T08:56:13+02:00

x^2 + 6x + 9 = (x)^2 + 2 \times 3 \times x + (3)^2

Donc x^2 + 6x + 9 = ( x+ 3)^2

 

36 - 12x + x^2 = (6)^2 - 2 \times 6 \times x + (x)^2

Donc 36 - 12x + x^2 = (6 - x)^2

 

100 - 4x^2 = (10)^2 - (2x)^2

Donc 100 - 4x^2 = (10 - 2x)(10 + 2x)

 

En espérant t'avoir aidé.